Role of lamellar thickening in thick lamellae formation in isotactic polypropylene when crystallizing under flow and pressure - Yang, Shu-Gui; Lei, Jun; Zhong, Gan-Ji; Xu, Jia-Zhuang; Li, Zhong-Ming (Polymer (Guilford), 2019)
Lamellar thickening of semicrystalline polymers is a fascinating subject in the realm of polymer physics as lamellar thickness plays a vital role in deciding the performance of polymer products. Whereas, regarding the processing of semicrystalline polymers where both the flow and pressure exist, the mystery of lamellar thickening has not been revealed yet. Here, the lamellar thickening of isotactic polypropylene (iPP) crystallizing under flow (30 s−1) and pressure (100 MPa) is studied by using a custom pressuring and shearing device (PSD). IPP crystallizing under flow and pressure has manifested a large lamellar thickening rate, where the lamellar thickness increases from 24  to 31 nm within a very short period of time (3000 s). The increased portion of lamellar thickness (7 nm) is more than one quarter of the original lamellae. The fast lamellar thickening behavior of iPP is shown to be occurred only under the coexistence of flow and pressure. Conversely, the lamellar thicknesses for both the iPP crystallized under the sole effect of flow (7.0 nm) and pressure (7.5 nm) remain unchanged within the same period of time. Furthermore, the activation energy of lamellar thickening for iPP crystallizing under flow and pressure is 180.1 kJ/mol, substantially below that for iPP quiescently crystallizing at atmosphere pressure (460.7 kJ/mol). The fast lamellar thickening behavior for iPP crystallizing under flow and pressure is shown to be related with the flow-induced oriented α-parent lamellae, which are composed by regularly arranged polymer chains and have a low energy barrier for molecular chains translating along the chain axis. The current study pioneers the probing into lamellar thickening of iPP crystallizing under the coexistence of flow and pressure, and suggests a promising method to fabricate high performance polymer products with thick lamellae. [Display omitted] •Flow and pressure jointly induced α-form thick lamellae in iPP.•Lamellar thickening played a key role in the formation of α-form thick lamellae.•iPP crystallization under flow and pressure showed a fast lamellar thickening.